Motivational factors and retention of talented managers - Azra Ahmić; Elvir Čizmić (Business Systems Research (BSR), 2021)
Background: In a contemporary fast-changing world, companies are facing growing global competition, volatile markets, altered workforce structure, and another technological reshifting, which generates enormous pressure on them to improve their business performance and imposes the necessity to highlight practices of talent management more seriously. Objectives: In this study we explore interrelations between attraction/work motivational factors and talent retention, observed through talent engagement. Methods/Approach: The methodology in this research focuses on the comprehensive resource-based view and encompasses quantitative analysis based on data gathered from talented managers in Bosnia and Herzegovina. Results: The research results unveiled that talents were attracted to work for current companies primarily because of: good salary and company goodwill. The top three prevalent work motivational factors for talents included: (1) comfortable work environment, (2) enough autonomy and creativity in working and deciding, and (3) work-life balance. Furthermore, talent motivational factors related to talent retention in a statistically significant positive way. Conclusions: This study furnishes available talent research and theory by relating attraction/work motivational factors to talent engagement; and by introducing the fundamental motivational factors which are of monumental importance for retaining talented managers in Bosnia and Herzegovina.
Keywords: J24; O15; 330; human resource management; talent motivation; talent management; talent attraction; talent retention